“Your Own Sensitivity, At Least”: Remembering the Postwar Poet Ibaragi Noriko, an Appreciation and Four Translations - Greg Vanderbilt (Asia-Pacific Journal, 2011)
This month marks the fifth anniversary of the death of the postwar poet Ibaragi Noriko (1926-2006). She was prepared: three months earlier, at age 79, she had written out a farewell letter and had it printed, ready to send to some two hundred of her friends and correspondents. Leaving blanks for the date (February 17, 2006, though it was two days later when she was found in her bed) and cause of her death (a brain hemorrhage), she expressed her wishes that there be no funeral or memorial and that no flowers be sent to her now vacant suburban home. Instead she made one request: “If you will pause for a moment, just a moment, and say to yourself ‘So now she is gone…,’ that will be enough.”Among the first poets to emerge in a new generation (and often considered the first and best-known woman among them) after the 1945 defeat, Ibaragi was sui generis in a time when poets were part of rebuilding the imagination of a citizenry, seeking to “cultivate” (tagayasu, her favorite verb, she said) in the language, place, and time where they happened to make their homes. With her beret and dark-rimmed glasses, her ever-present slim cigarettes and mellow voice, and her keen, youth-filled observations, she cut an unforgettable figure to the end of her life. A comment she made in her last months may well be a fitting summation: “I never thought I would have any affiliation, but in the end I can say I was affiliated with the Japanese language.”